Proceedings of the 2016 International Conference on Biological Engineering and Pharmacy (BEP 2016) 2017
DOI: 10.2991/bep-16.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity and Physiological Effects of Combined Application of Poly-Hexamethylene Biguanide Hydrochloride and 1-bromo-3-chloro-5, 5-dimethylimidazolidine-2, 4-dione on Staphylococcus aureus

Abstract: Abstract-Poly-hexamethylene biguanide hydrochloride (PHMB) and 1-bromo-3-chloro-5,5-dimethylimidazolidine-2,4-dione (BCDMH) are widely used for surface disinfection. Here, we examined the bactericidal effects of the mixture of PHMB and BCDMH (named PB) combined in different ratios on S. aureus, and studied effects of temperature, pH and bovine serum albumin (BSA , as organic interferent) on PB bactericidal activity with suspension quantitative germicidal method. We also observed surface structure changes and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…PB is a combined disinfectant established in our laboratory, and it is formed with PHMB and BCDMH. We have studied the PB bactericidal effects on E. coli , Pseudomonas aeruginosa (unpublished data), and S. aureus [ 7 ]. The related results showed that PB has relatively optimal bactericidal activity at relatively low concentration [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PB is a combined disinfectant established in our laboratory, and it is formed with PHMB and BCDMH. We have studied the PB bactericidal effects on E. coli , Pseudomonas aeruginosa (unpublished data), and S. aureus [ 7 ]. The related results showed that PB has relatively optimal bactericidal activity at relatively low concentration [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have studied the PB bactericidal effects on E. coli , Pseudomonas aeruginosa (unpublished data), and S. aureus [ 7 ]. The related results showed that PB has relatively optimal bactericidal activity at relatively low concentration [ 7 ]. In this study, we try to examine its fungicidal, metal corrosive, and mutational effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation